Effects of feeding excess dietary crude protein from soybean meal and dried distillers grains with solubles on nursery pig performance - S M Williams; C B Paulk; S Issa; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2010)
Two experiments were conducted to determine the effects of feeding excess dietary CP to nursery pigs. In Exp. 1, a total of 105 nursery pigs (PIC TR4 x 1050, initially 22.9 lb and 35 d of age) were used in a 21-d growth assay to determine the effects of feeding excess CP from soybean meal to nursery pigs. The pigs were fed a pelleted commercial starter diet for the first 14 d after weaning, and the experimental treatments were fed for the next 21 d. Treatments consisted of 3 corn-soybean meal-based diets formulated to different CP levels: (1) 22.5%, (2) 25%, and (3) 27.5% CP. Increasing CP from 22.5 to 27.5% had no effect (P>0.19) on ADG, ADFI, or F/G. In Exp. 2, a total of 105 nursery pigs (PIC TR4 x 1050, initially 22.1 lb and 35 d of age) were used in a 21-d growth assay to determine the effects of excess CP from dried distillers grains with solubles (DDGS) on nursery pig growth. The pigs were fed a pelleted commercial starter diet for the first 14 d after weaning and the experimental treatments for the next 21 d. Treatments were corn-soybean meal-based diets formulated to 22.9 and 25% CP and a diet with 30% DDGS formulated to 25% CP. Increasing the CP concentration had no effect (P>0.12) on ADG, ADFI, or F/G. However, pigs fed the DDGS had poorer (P<0.04) F/G compared to pigs fed the corn-soybean meal-based diet formulated to 25% CP. Our data suggest that nursery pigs can tolerate CP levels up to 27.5% without negative effects on growth performance. Additionally, the inclusion of 30% DDGS in nursery pig diets did not have a significant impact on ADG or ADFI, but did negatively affect F/G.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Dried distillers grains with solubles; Excess crude protein; Soybean meal